Variation in wing morphology is related to breeding environment in a high‐elevation specialist bird. (4th October 2022) - Ceresa, Francesco; Vitulano, Severino; Pes, Michele; Tomasi, Laura; Brambilla, Mattia; Kvist, Laura; Pedrini, Paolo; Anderle, Matteo; Hilpold, Andreas; Kranebitter, Petra
Abstract : The morphology of bird wings is subject to a variety of selective pressures, including migration, predation, habitat structure and sexual selection. Variation in wing morphology also occurs at the intraspecific and intrapopulation level, and can be related to sex, age, migration strategy and environmental factors. The relationship between environment and intraspecific variation in wing morphology is still poorly understood. In this work, we studied the relationship between wing morphology and breeding environment in a high‐elevation specialist bird, the water pipit Anthus spinoletta . We calculated wing isometric size, pointedness and convexity of 84 birds mist‐netted at breeding sites in year 2021 in the European Alps. We then searched for associations between these traits and potentially relevant breeding site characteristics (vegetation structure, elevation, latitude). For all wing traits, sex and one or more environmental factors best explained the variation, with environmental factors explaining between 3 and 8% of the variation. Wing size was negatively related to tree cover and wing convexity was negatively related to bush cover. Elevation contributed to explain variation in wing pointedness, but the direction of its effect was unclear. The negative relationship between wing size and tree cover could be due to intraspecific competition, i.e. to the relegation of smaller winged low‐quality individuals in marginal grassland areas. Higher wing convexity could improve predator escape ability in areas with scarce protecting vegetation, with possible effects on habitat choice. These findings represent one of the few demonstrated cases of wing morphology–environment relationships at the intraspecific level.